PENERAPAN POMPA HIDRAM METODE PARALEL DI DESA PUNGGUK BERINGIN BENGKULU TENGAH - Irkhos .; Suhendra .; Sukisno . (DHARMA RAFLESIA, 2017)
The program is implemented in Pungguk Beringin Merigi Kelindang Bengkulu Tengah. The purpose of this program is to provide the knowledge and skills of rural communitiesPungguk Beringin on utilization Hydraulic ram. Participants were representatives ofcommunity activities. The solution provided is the application of Parallel MethodsHydraulic ram. Through this program generated installation Hydraulic ram diameter of 2inches with 10 liters of effluent water discharge to drain the water to a height of 50 metersby 150 meters.Keywords: Hydraulic ram pump, Parallel Methods, Pungguk Beringin